ADR in Sport on the Example of Association Football in Poland and Ukraine - Sławicki, Piotr; Kryzhanivskyi, Viktor (Review of European and Comparative Law, 2023)
The subject of this article is the use of ADR in sports disputes in association football under the Polish and Ukrainian law. Professional and amateur sport generates various types of disputes related to both disciplinary and civil cases, an example of which may be disputes arising during the execution of contracts binding players and football clubs. In the first part, the scope of disputes that are subject to ADR in association football is outlined. The next part presents legal solutions adopted under the Polish law in this respect, of which the activity of the Football Arbitration Court of the Polish Football Association is a particular example. The last chapter is devoted to the Ukrainian perspective on the resolution of disputes in association football.